PENGARUH VARIABEL OPERASI PADA PROSES MODIFIKASI PATI GARUT DENGAN METODE CROSS LINKING PENGGANTI TEPUNG TERIGU SEBAGAI BAHAN BAKU PADA INDUSTRI BAKERY - Rakhmawati, Putri; Octaviani, Risa Dwi; Santosa, Herry (TEKNIK, 2014)
[Title: Operating Variables Effects on Process Modification of Arrowroot Startch by Cross Linking Method for Substituting Wheat Flour as Bakery Industry Raw Material] Arrowroot starch is local food comodity that has potential for many use.The advantage of arrowroot starch are free gluten and low glisemic index. But, arrowroot starch has disadvantage swelling power and solubility doesnâ€™t criteria. In this study, an attempt is made to change the arrowroot starch raw material for bakery industry by using cross-linking methods. The purpose of this research is to study the effect of reaction temperature, reaction time, and volume gingerol of swelling power and solubility. To achieve the goal of research through three stages: (1) The characteristic of arrowroot, (2) The phase of modified arrowroot starch with method Cross Linking is done to change the properties of arrowroot starch in accordance with the specification qualify as bakery industry raw materials, (3) Analysis phase to modified arrowroot starch products which include swelling power and solubility. To achieve swelling power and solubility for raw material bakery industry, cross linking process to Arrowroot strach better are reaction temperature at 400C, reaction time at 90 minutes and oleoresin volum at 0,3 ml.Â